2015
DOI: 10.1158/1541-7786.mcr-14-0275-t
|View full text |Cite
|
Sign up to set email alerts
|

ERG Oncoprotein Inhibits ANXA2 Expression and Function in Prostate Cancer

Abstract: Overexpression of ERG in the prostate epithelium, due to chromosomal translocations, contributes to prostate tumorigenesis. Here, analysis of ERG siRNA-treated prostate cells harboring the endogenous TMPRSS2-ERG fusion revealed an inverse relationship between ERG and Annexin A2 (ANXA2) expression at both the RNA and protein level. ANXA2, a Ca2+-dependent and phospholipid–binding protein, is involved in various cellular functions, including maintenance of epithelial cell polarity. Mechanistic studies defined th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…A total of 135 probe sets of this CodeSet target transcripts from 121 oncogenes, tumor suppressors, and gene fusion variants associated with prostate cancer and cancer in general. These genes were selected based on their association with cancer, specifically prostate cancer, according to the following criteria, supported by at least two publications: (1) have significant differential gene expression in prostate tumor versus normal comparison based on microarray gene expression profiling (data accessible at NCBI GEO database, accession GSE32448 [24]), including ERG [25, 26], ERG8 [27, 28], ANXA2 [29, 30], MYO6 [31, 32] and MAOA [32, 33]; (2) are regulated by androgen, such as AMACR [25, 34, 35], PSGR [36, 37], PCGEM1 [38, 39], [40, 41], and NKX3.1 [42, 43]; (3) are associated with prognosis of prostate cancer, such as AR [44, 45], EZH2 [46, 47], C-MYC [48, 49], PTEN [50, 51], and NCOA2 [52, 53]; (4) are associated with the ETS family of transcription factors detected in GSE32448 [54, 55]; (5) are commonly rearranged in prostate cancer [26, 56, 57]; (6) are involved in prostate cancer cell invasion, such as SPINK1 [58, 59], TFF3 [60, 61], MMP2 and MMP9 [62, 63]; (7) or are associated with multiple malignancies involving PDGF [64], RAS [65], VEGF [66], EGFR [67], TP53 [65, 68], Interleukin [52], and JAK/STAT signaling pathways [69, 70]. An additional 16 probe sets target five genes that distinguish prostate epithelial from stromal cells [7174], and 11 house-keeping genes with minimal tumor-normal differential expression identified through gene expression profiling [24] were included as controls.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 135 probe sets of this CodeSet target transcripts from 121 oncogenes, tumor suppressors, and gene fusion variants associated with prostate cancer and cancer in general. These genes were selected based on their association with cancer, specifically prostate cancer, according to the following criteria, supported by at least two publications: (1) have significant differential gene expression in prostate tumor versus normal comparison based on microarray gene expression profiling (data accessible at NCBI GEO database, accession GSE32448 [24]), including ERG [25, 26], ERG8 [27, 28], ANXA2 [29, 30], MYO6 [31, 32] and MAOA [32, 33]; (2) are regulated by androgen, such as AMACR [25, 34, 35], PSGR [36, 37], PCGEM1 [38, 39], [40, 41], and NKX3.1 [42, 43]; (3) are associated with prognosis of prostate cancer, such as AR [44, 45], EZH2 [46, 47], C-MYC [48, 49], PTEN [50, 51], and NCOA2 [52, 53]; (4) are associated with the ETS family of transcription factors detected in GSE32448 [54, 55]; (5) are commonly rearranged in prostate cancer [26, 56, 57]; (6) are involved in prostate cancer cell invasion, such as SPINK1 [58, 59], TFF3 [60, 61], MMP2 and MMP9 [62, 63]; (7) or are associated with multiple malignancies involving PDGF [64], RAS [65], VEGF [66], EGFR [67], TP53 [65, 68], Interleukin [52], and JAK/STAT signaling pathways [69, 70]. An additional 16 probe sets target five genes that distinguish prostate epithelial from stromal cells [7174], and 11 house-keeping genes with minimal tumor-normal differential expression identified through gene expression profiling [24] were included as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Annexin A2 is proved to be implicated in various cancers, including HCC. 17,[35][36][37][38] For example, Zhang et al reported that shRNA-mediated silencing of ANXA2 suppresses the invasion, migration and tumourigenic potential of hepatoma cells and may thus be utilized as a target of future molecular therapies. 39 As ANXA2 binds with LUCAT1, and considering the desperate need to find a better therapeutic target for HCC patients, we designed subsequent experiments to determine the mechanism of ANXA2 and LUCAT1.…”
Section: Discussion and Con Clusionmentioning
confidence: 99%
“…Therefore, these molecules are expected to function as autoantigens, with their exposure as antigens attributable to various stimuli such as hypoxia, infection, or ischemia. In addition, annexin A2 and Hsp90 have been reported to be associated with the development of prostate cancer by promoting the growth process 2629 . These reports indicate that annexin and Hsp90 may be associated with the BPH growth process in an as yet unknown manner.…”
Section: Discussionmentioning
confidence: 99%